Penerapan Transparansi Lembaga Pengelola Zakat (Studi Pada Lembaga Amil Zakat Dan Unit Pengelola Zakat Baznas Provinsi Banten) - Fatoni, Ahmad; Fakhrudin, Muhamad (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2023)
As an institution that manages social funds, transparency is something that must be met for the Amil Zakat Institution and the Zakat Management Unit. Public distrust of zakat management institutions is one of the causes of the gap between zakat potential and the realization of zakat collection in Banten Province. This study aims to analyze the implementation of the transparency of the Amil Zakat Institution and the Baznas Zakat Management Unit in Banten Province. This study used qualitative research methods. The results showed that the Amil Zakat Institute in Banten province had implemented financial transparency, management, and programs in zakat management activities. Similarly, the principles of transparency, accountability, effectiveness, and collaborative distribution have been applied by the Zakat Management Unit of Baznas Banten Province.